Reconstrução do ligamento cruzado posterior em banda dupla: resultados e comparação entre diferentes enxertos autólogos - Mestriner, Marcos Barbieri [UNIFESP] (2019)
Posterior cruciate ligament (PCL) reconstruction presents controversies, such as the number of bands to be reconstructed (single band versus double band) and the choice of graft with better mechanical and biological properties. Objective: To demonstrate and compare the results of knee function and stability in patients with PCL injuries submitted to the technique of double-band transtibial PCB reconstruction using two types of autologous grafts. Method: Fifty-two patients (N = 52) with isolated PCL lesions or associated with multiligament lesions submitted to double-band transtibial reconstruction were evaluated; ipsilateral quadriceps and semitendinous tendon grafts (group 1) were used in 34 patients and 18 bilateral flexor tendon grafts (gracile and semitendinosus). The criteria for the function and stability evaluation were the objective IKDC, the Lysholm questionnaire, the posterior drawer test and the KT-1000TM evaluation. All patients were evaluated preoperatively and postoperatively with a minimum follow-up of two years. Results: when comparing the preoperative and postoperative periods, there was a statistically significant improvement (p <0.05) in all studied variables, without differences between the grafts used. When comparing the results between isolated and combined lesions, no significant difference was observed. Considering the frequency of the best results, it was observed that group 2 patients with combined lesions presented superior results in the objective IKDC. Conclusion: The patients submitted to the PCB double-band transtibial reconstruction technique showed significant improvement, both in functional scores and in the reestablishment of posterior knee stability, without differences in the type of graft used. Comparison of the best outcomes showed that there was superiority of objective outcomes in patients with multi-ligament injuries who underwent bilateral flexor tendon reconstruction (group 2).